Comparing the attitudes of four groups of stakeholders from Quebec, Canada, toward extending medical aid in dying to incompetent patients with dementia. (29th April 2019) - Bravo, Gina; Trottier, Lise; Rodrigue, Claudie; Arcand, Marcel; Downie, Jocelyn; Dubois, Marie‐France; Kaasalainen, Sharon; Hertogh, Cees M.; Pautex, Sophie; Van den Block, Lieve
Abstract : Objective: The Canadian province of Quebec has recently legalized medical aid in dying (MAID) for competent patients who satisfy strictly defined criteria. The province is considering extending the practice to incompetent patients. We compared the attitudes of four groups of stakeholders toward extending MAID to incompetent patients with dementia. Methods: We conducted a province‐wide postal survey in random samples of older adults, informal caregivers of persons with dementia, nurses, and physicians caring for patients with dementia. Clinical vignettes featuring a patient with Alzheimer's disease were used to measure the acceptability of extending MAID to incompetent patients with dementia. Vignettes varied according to the stage of the disease (advanced or terminal) and type of request (written or oral only). We used the generalized estimating equation (GEE) approach to compare attitudes across groups and vignettes. Results: Response rates ranged from 25% for physicians to 69% for informal caregivers. In all four groups, the proportion of respondents who felt it was acceptable to extend MAID to an incompetent patient with dementia was highest when the patient was at the terminal stage, showed signs of distress, and had written a MAID request prior to losing capacity. In those circumstances, this proportion ranged from 71% among physicians to 91% among informal caregivers. Conclusion: We found high support in Quebec for extending the current MAID legislation to incompetent patients with dementia who have reached the terminal stage, appear to be suffering, and had requested MAID in writing while still competent.